Clostridium difficile Infection in Solid Organ and Haematopoietic Stem Cell Transplant Recipients. (4th October 2017) - Ilett, Emma Elizabeth; Sengeløv, Henrik; Sørensen, Søren Schwartz; Gustafsson, Finn; Perch, Michael; Rasmussen, Allan; Lundgren, Jens; Frimodt-Møller, Niels; Helleberg, Marie
Abstract: Background: Solid organ transplantation (SOT) and haematopoietic stem cell transplantation (HSCT) recipients have a higher incidence of Clostridium difficile infection (CDI) in comparison to non-transplantation patients. We examined rates of CDI before and after SOT or HSCT, as well as rates of recurrent CDI. Methods: A retrospective study of adults >18 years of age undergoing SOT or HSCT between January 1, 2010 and February 21, 2017, at a large tertiary transplant center in Copenhagen, was conducted. Patients were followed using national electronic data capture from 6 months prior to transplantation until closure of the study period. Relative risks were estimated by Poisson regression analyses, adjusted for age, gender, and year of transplantation. CDI occurring up to 6 months prior to transplantation was assessed as a risk factor for post-transplantation CDI. Results: Among 1, 150 SOT and 586 HSCT recipients, a total of 252 (15%) developed a CDI after transplantation. Incidence rate (IR)s were highest within the first 2 months post-transplantation, especially among those undergoing liver, lung and myeloablative HSCT (Table 1 and Figure 1). Pre-transplantation rates of CDI were similar to those seen after the first 2 months post-transplantation. There was a greater risk of developing early CDI in SOT, but not in HSCT, recipients who had experienced a pre-transplantation CDI (IR ratio (IRR) 6.1 (95% confidence interval (CI) 2.2–17.1) and 1.5 (95% CI 0.5–4.1), respectively). Rates of recurrent CDI after transplantation (i.e., the second CDI after transplantation) were comparable for SOT and HSCT recipients (Table 1). Conclusion: Transplantation type, close proximity to time after transplantation, and a CDI episode prior to transplantation (in SOT recipients) influences the risk of CDI. All transplantation types have a markedly higher risk of CDI the first 2 months post-transplantation, but not subsequently, with the highest risk among liver, lung and HSCT recipients. These findings warrant further investigation into the causes and risk factors of CDI in HSCT and SOT recipients, respectively, and once accomplished, open the possibility to develop preventive measures close to time of transplantation for those identified to be at excess risk. Disclosures: All authors: No reported disclosures.